Activation of astrocytic sigma‐1 receptor exerts antidepressant‐like effect via facilitating CD38‐driven mitochondria transfer. Issue 11 (27th May 2020) - Wang, Yun; Ni, Jing; Gao, Tianyu; Gao, Ce; Guo, Lin; Yin, Xiaoxing
Abstract: Despite sigma‐1 receptor (Sig‐1R) is a promising therapeutic target in depression, little is known regarding the cellular mechanisms underlying its antidepressant responses. Here, we demonstrated that astrocyte can be a direct cellular target of Sig‐1R exerting antidepressant‐like effect. In multiple behavioral models including forced swimming test (FST), tail suspension test (TST), open field test (OFT), and chronic unpredictable mild stress (CUMS), inhibition of astrocyte function blocked pharmacological Sig‐1R activation‐induced antidepressant‐like effect, while specific activation of astrocytc Sig‐1R by adeno‐associated virus (AAV) was sufficient to produce antidepressant‐like effect. In depression‐related cellular tests, Sig‐1R agonist or lentivirus‐stimulated astrocyte conditioned medium (ACM) promoted neuronal neurite outgrowth, dendritic branch, and survival. Mechanismly, stimulation of Sig‐1R enhanced the expression of CD38 via activation of extracellular regulated protein kinases 1/2 (ERK1/2), resulting in facilitating mitochondrial transfer from astrocyte. Furthermore, blockage of CD38‐driven astrocyte transferring mitochondria in vivo and in vitro reversed the antidepressant‐like effect of pharmacological Sig‐1R activation. Thus, this study sheds light on the cellular mechanism of Sig‐1R activation producing antidepressant‐like effect. These data present the first evidence that enhancement of Sig‐1R action on astrocytes entirely exerts antidepressant‐like effect, indicating that specific activation of astrocytic Sig‐1R may provide a new approach for antidepressant drug development. Main Points: Astrocyte is a direct cellular target of Sig‐1R producing antidepressant‐like effect. Activation of astrocytic Sig‐1R is sufficient to exert antidepressant‐like effect. Activation of Sig‐1R promotes astrocyte mitochondria transfer